2023
DOI: 10.3390/pathogens12010099
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Biological Control of the Sugar Beet Weevil Asproparthenis punctiventris with the Fungus Metarhizium brunneum: New Application Approaches

Abstract: The mass occurrence of the sugar beet weevil (Asproparthenis punctiventris, previously Bothynoderes punctiventris) has been endangering sugar beet cultivation in Austria for centuries. Exacerbated by climatic and political changes (warmer, drier spring and limited access to chemical pesticides), new approaches are needed to counter the problem. The aim of our work was to test whether the bioinsecticide Metarhizium brunneum Ma 43 (formerly M. anisopliae var. anisopliae BIPESCO 5/F52) can be used as a sustainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Entomopathogenic nematodes [7,13] or entomopathogenic fungi, such as Metarhizium brunneum [14], could be used for the biological control of A. punctiventris. Although these initial studies have confirmed the efficacy of the natural antagonists, more research is needed before they can be used in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Entomopathogenic nematodes [7,13] or entomopathogenic fungi, such as Metarhizium brunneum [14], could be used for the biological control of A. punctiventris. Although these initial studies have confirmed the efficacy of the natural antagonists, more research is needed before they can be used in practice.…”
Section: Introductionmentioning
confidence: 99%